Social capital in Ukraine's economic transformation - Piddubny, V.; Chepurco, G. (Социология: теория, методы, маркетинг, 2017)
Today, Ukraine has no alternative but to take a path of innovative changes as a necessary step for enhancing the competitiveness of the national economy. Against a backdrop of fierce global competition, restricted financial resources and geopolitical tensions, social capital is assuming particular importance. Though being an intangible asset of the society, it is helpful in searching for promising economic management models. The phenomenon of social capital also reveals itself under extreme conditions, as it was during the Revolution of Dignity in 2013-2014 when lots of Ukrain ians were participating in numerous civic initiatives and defending public interests at various stages of social organisation within an innovative economic transformation. The authors draw attention to the new socio-economic environment which in a certain way spurs innovative development of the national economy, thereby facilitating Ukraine’s integration into the European Union.